Pertanggungjawaban Perdata atas Pelanggaran Kode Etik Keilmuan: Analisis Filsafat Ilmu - Mahlil Mahlil; Nukman Hasibuan; Mukhlis Mukhlis; Marwan Marwan; Nazaruddin Nazaruddin; Dwi Fitri; Iskandar Iskandar (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2026)
This study aims to examine the construction of civil liability for breaches of scientific codes of ethics through the perspectives of philosophy of science and civil law doctrine. Employing a qualitative library-based methodology, this research adopts a normative juridical approach enriched by conceptual and philosophical analysis. The findings indicate that scientific codes of ethics constitute ethical–scientific norms that may acquire juridical relevance when their violation fulfills the elements of a tort (unlawful act), namely fault, damage, and causal relationship. In this context, civil liability functions as a corrective and restorative mechanism that strengthens scientific accountability without undermining academic freedom.